In Situ Remediation of Chlorinated Solvent Plumes - Stroo, Hans F.; Stroo, Hans F.; Ward, C. Herb.; Ward, C. Herb. (SERDP ESTCP Environmental Remediation Technology,, 2010)
In Situ Remediation of Chlorinated Solvent Plumes H.F. Stroo & C.H. Ward Editors This volume presents a critical analysis and timely synthesis of the past two decades of intensive research, development and demonstrations on the in situ remediation of chlorinated solvent plumes. The intended audiences include the decision makers, practicing engineers and hydrogeologists who will select, design and operate these remedial systems, as well as the researchers seeking to improve the current state of the science and technology. Our hope is that this volume will serve as a useful resource to assist remediation professionals in applying and developing these technologies as effectively as possible. Topics addressed in this volume include: An overview of the current state of understanding of chlorinated solvents remediation. A summary of the chemistry of solvents, the physical, chemical and biological processes that underpin the most frequently employed remediation technologies, and the engineering and implementation issues that influence their efficacy. A discussion of site characterization, source zone and plume management, and modeling strategies and tools. An analysis of the advantages, performance and relative costs of a range of remedial technologies, including bioremediation technologies such as monitored natural attenuation, biostimulation and bioaugmentation for anaerobic degradation of chlorinated solvents; and physical-chemical technologies such as air sparging, chemical oxidation and reduction, barrier walls, and in-well treatment. A cost assessment of the most frequently used technologies, with case studies of several template sites and analyses of the capital costs, as well as costs for laboratory testing, pilot-scale demonstration, design, system operation, monitoring and maintenance during operations, and demolition and restoration after remediation. In addition, analogous cost data are presented for pump-and-treat systems for each template site to illustrate the potential cost savings associated with the use of alternative approaches. A summary of emerging technologies such as phytoremediation and electrolytic reactive barriers to illustrate their current stage of maturity and the potential applicability of these approaches for specific situations. An assessment of the research needed to more cost-effectively address what remains of a multi-billion dollar legacy environmental contamination problem. Each chapter in this volume has been thoroughly reviewed for technical content by one or more experts in each of the subject areas covered. The editors and chapter authors have produced a well-written and up-to-date treatise that we hope will be a useful reference for decision-makers, practitioners and developers of advanced technologies for in situ remediation of chlorinated solvent plumes.